2013
DOI: 10.3109/00016489.2012.758388
|View full text |Cite
|
Sign up to set email alerts
|

Expression of HMGA1 and Ezrin in laryngeal squamous cell carcinoma

Abstract: (1) IHC revealed that the positive rate of HMGA1 protein was 68.0% (34/50), 53.3% (16/30), and 13. 3% (4/30) in LSCC, atypical hyperplasia of larynx, and laryngeal polyp (p < 0.05), and the positive rate of Ezrin protein was 64.0% (32/50), 50.0% (15/30), and 23.3% (7/30) (p < 0.01), respectively. (2) Real-time PCR demonstrated that the mean relative mRNA expression levels of HMGA1 in LSCC and in normal tissues were 2.41 ± 0.40 and 1.05 ± 0.18, respectively (p < 0.01). The mRNA levels of Ezrin in LSCC and in no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 13 publications
1
8
0
Order By: Relevance
“…Similar to Wang et al report, HMGA1 expression also correlated with tumor size, tumor invasion, and histological grade in human pituitary adenomas [26]. In laryngeal squamous cell carcinoma, HMGA1 overexpression positively associated with clinical stage, lymph node metastasis, and histological grade [27]. These studies consistently suggest that overexpressed HMGA1 may play an unfavorable role in breast cancer patients.…”
Section: Discussionsupporting
confidence: 56%
“…Similar to Wang et al report, HMGA1 expression also correlated with tumor size, tumor invasion, and histological grade in human pituitary adenomas [26]. In laryngeal squamous cell carcinoma, HMGA1 overexpression positively associated with clinical stage, lymph node metastasis, and histological grade [27]. These studies consistently suggest that overexpressed HMGA1 may play an unfavorable role in breast cancer patients.…”
Section: Discussionsupporting
confidence: 56%
“…Our results may indicate that HMGA1 plays significant roles in NSCLC progression, including tumor proliferation, invasion, and metastasis. Similar to Wang et al's report, HMGA1 overexpression positively associated with clinical stage, lymph node metastasis, and histological grade in patients with laryngeal squamous cell carcinoma [29]. In human pituitary adenomas, HMGA1 expression also correlated with tumor size, tumor invasion, and histological grade [19].…”
Section: Discussionmentioning
confidence: 59%
“…This transformation may weaken intercellular adhesion of normal cells and enhance the adhesion between tumor cells and normal cells, which promote tumor metastasis. [ 15 ] According to the author Zhai et al ., the activation of Rac 1 pathway by ezrin causes hepatocyte growth factor to induce tyrosine phosphorylation of E-catenin and X-catenin, inhibits the function of E-cadherin, and leads to redistribution of E cadherin in cytoplasm and on cell membrane. [ 16 ]…”
Section: Discussionmentioning
confidence: 99%
“…Phosphorylation of ezrin at its tyrosine residues activates the PI3-kinase/Akt pathway, thereby prevents apoptosis of tumor cells. [ 15 ] Schlecht et al . observed that high cytoplasmic ezrin expression indicates the altered expression of antiapoptotic genes (BIRC2, CCDC50, and TGM2) and proapoptotic genes (EDARADD), resulting in survival rather than cell death.…”
Section: Discussionmentioning
confidence: 99%